2015
DOI: 10.1111/jocn.13009
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of medications for Parkinson's disease: a qualitative description

Abstract: Nurses may have a role to assess individuals' beliefs and concerns about antiparkinsonian medication therapy and to provide adequate information to assist with the decision about Parkinson's disease symptom management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The app was helpful as people with PD respond positively to psychological support and trust from healthcare professionals including nurses. 32,33,39 To increase the retention rate, utilizing peer groups to facilitate use of the Yon PD app can be considered. Social support can facilitate app use.…”
Section: Discussionmentioning
confidence: 99%
“…The app was helpful as people with PD respond positively to psychological support and trust from healthcare professionals including nurses. 32,33,39 To increase the retention rate, utilizing peer groups to facilitate use of the Yon PD app can be considered. Social support can facilitate app use.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about real or perceived side effects, dislike for drug interventions, and general skepticism about drugs were cited as person-level barriers [32]. Trust of healthcare professionals however can overcome these problems and facilitate pharmacological therapy [33]. Preference for naturopathic remedies can also be a barrier to medication non-adherence [33].…”
Section: Ability To Engage In Healthcarementioning
confidence: 99%
“…Trust of healthcare professionals however can overcome these problems and facilitate pharmacological therapy [33]. Preference for naturopathic remedies can also be a barrier to medication non-adherence [33]. In particular, mental health treatments may be avoided due to fears about dependency on medication [34] and tendencies to under-report non-motor symptoms or their severity [27,34,35].…”
Section: Ability To Engage In Healthcarementioning
confidence: 99%
“…The guideline considered the literature until April 2014. Several papers have appeared since the publication of the guideline [16][17][18][19][20]. None of these studies existed of an RCT, and one systematic review reported the state of research related to PD conducted by nurse scientists during a 10-year period [20].…”
Section: Formal Approvalmentioning
confidence: 99%